A novel encryption compression scheme using Julia sets. (17th May 2019) - Prasad, Bhagwati; Mishra, Kunti
The intent of the paper is to propose a novel fractal-based encryption compression scheme using logistic map and Julia sets. In our study of medical images, we obtain significant lossless compression and secure encryption of the image data. The proposed technique is expected to be useful for the transmission of various confidential image data relating to medical imaging, military and other multimedia applications.